Estudo dos desvios de fala em pré-escolares de escolas públicas estaduais de Santa Maria - RS - Casarin, Maisa Tatiana (2006)
This study aimed to estimate the prevalence of speech disorder in a sample of children from a public state school, verify the prevalence of disorder in according to sex; classify the deviation according to type and severity; verify the occurrence of delay in language acquisition in children with phonological disorder; characterize the phonetic inventory and the phonological system of this sample, and verify which the most altered phonemes are. The sample was composed of 91 subjects of both sex, ranging from 5:7 and 7:5. All of them were submitted to speech-language evaluations and phonological assessments that were applied to determine the type and degree of severity of speech disorder as well as the phonetic inventory and the phonological system. For the statistical analysis Qui-Quadrado Test, Variance analysis, t-test and Kruskal-Wallis were used, with level of significance of 5% (p<0,05). Analyses were developed using SPSS 8.0 software. Amongst the 91 subjects 46 (70,3%) had speech disorder and the 27 other (29,7%) presented appropriate speech acquisition (GAFN). Considering the obtained on deviation type, the prevalence was of 18,55% for phonological deviation (GDFo), 2,10% for phonetic deviation (GDFe) and of 5,24% for phonological-phonetic deviation (GDFoFe). Association between delay in language acquisition process and the disorder type was not observed. It was noticed significant statistic association between: masculine gender and the group with speech disorder; the feminine gender and GAFN; GDFe and the tongue altered posture; GDFo and the incomplete phonetic inventory; GAFN and the complete phonetic inventory; GDFo and phonological system altered; GDFe and GAFN and the appropriate phonological system. The sounds with highest omission in the inventory were: /з /, /z/, /r/, /λ / e /g/ and /g/ for GDFo; and /r/,/g /, /z/, /∫/ and /λ / for GDFoFe. The groups GDFe and GAFN presented PCC significantly higher than GDFoFe. The phonemes with most alterations in the phonological system were: /r /, /λ/, /з /∫ / and /z/ for GDFo and /∫ /λ /, /, /r/, /g/ for GDFoFe. In both groups, the majority of subjects presented difficulties with the complex onset, and with the erasure of the rhotic consonants /r/ e /l/. As for the distinctive features it was verified that: GDFo and GDFoFe presented significant statistically altered number of features, more than GAFN; the most altered features for: [+voz] ®-voz], [-ant] ®[+ant], [+cont] ®[-cont], [-voc] ®[+voc] in GDFo and [-ant] ®[+ant], [+voz] ® [-voz], [+ant] ® [-ant] in GDFoFe. Therefore, this research shows that there is high prevalence on speech deviation/disorder in the group of preschoolers studied, and that the larger the number of missing sounds in the phonetic inventory the higher the disorder severity. Furthermore, the high number of alterations in the fricative class and the rhotic consonants suggest that the subjects who present phonological or phonological-phonetic disorders/deviations adopt similar strategies, however not identical to the ones used by children with appropriate phonological development because these classes of phonemes are, according to literature, the last to be acquired.